Social Media and Democracy in Africa: A Case Study of the Zimbabwe 2018 Harmonised Elections - Ncube, Meli (Centre for Film and Media Studies, 2022)
A political system that facilitates and encourages sincere and careful listening among its citizens will produce more democratic decisions. Yet, good listening is being almost completely ignored in that form of political conversation we know as democracy. As such, this thesis argues that due to an abundance of ‘digital citizens' owing to the proliferation of the internet and social media, a ‘democratic listening' approach to political deliberation has become urgent. However, the application of digital citizenship and democratic listening theories have been minimal in Africa's democratic framework. Accordingly, this thesis seeks to develop this neglected body of scholarship by submitting a case study of Zimbabwe's 2018 harmonised elections. In the African context, most countries principal criterion for democracy is the holding of elections and simply letting citizens' vote. Most of these African administrations also escape the demands of accountability and democratization by steadfastly manipulating legacy media – media originally distributed using a pre-internet medium i.e., print, radio and, television. With the advent of social media which has enabled citizens to access alternative sources of information, this aberrant principal criterion of democracy is now being challenged. The thesis locates itself within digital methods that incorporate qualitative research methods. It makes use of the available digital objects such as the like, share, and retweet buttons to explore societal changes and cultural conditions by investigating online data. The data for analysis is gathered from the social media platforms, Twitter, Facebook, and WhatsApp Messenger. Twitonomy which was developed precisely for Twitter research and offers detailed and visualised analytics of tweets and hashtags is used for data gathering on Twitter. For Facebook, the now defunct Netvizz is used for textually mining data off the platform and on WhatsApp Messenger, an ethnographical approach is exercised. The findings confirm that in Zimbabwe and Africa, social media have emerged as a space for mobilising resistance to authoritarianism and failed promises from elections. Although, African administrations exercise listening as a rhetorical exercise undertaken for instrumental reasons to boost their popularity when they are in a state of decline, social media are now a viable alternative public sphere that democratises political space.